2016
DOI: 10.1186/s40900-016-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in primary care research - an example of ensuring its sustainability

Abstract: BackgroundThe international literature on patient and public involvement (PPI) in research covers a wide range of issues, including active lay involvement throughout the research cycle; roles that patients/public can play; assessing impact of PPI and recommendations for good PPI practice. One area of investigation that is less developed is the sustainability and impact of PPI beyond involvement in time-limited research projects.MethodsThis paper focuses on the issues of sustainability, the importance of instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 6 publications
3
92
0
Order By: Relevance
“…Drawing upon previously identified frameworks identifying challenges of involving PPIE in research, Table summarises common challenges when involving PPIE in research, as well as suggestions for researchers. Unresolved challenges could result in superficial involvement, lack of meaningful impact, disregard of the public's potential contribution to the research project, as well as other ethical concerns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drawing upon previously identified frameworks identifying challenges of involving PPIE in research, Table summarises common challenges when involving PPIE in research, as well as suggestions for researchers. Unresolved challenges could result in superficial involvement, lack of meaningful impact, disregard of the public's potential contribution to the research project, as well as other ethical concerns.…”
Section: Discussionmentioning
confidence: 99%
“…The structure and operations of the PPIE team within the Research Institute have been reported elsewhere. 17 Individuals from the previous PPIE group were invited to participate in the present research. Interested individuals and consequently the PPIE group for this research consisted of an older female adult with self-harm history, a male carer and a female support worker with previous experience of self-harm.…”
Section: Me Thodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into PPI has mainly focused on the mechanisms of PPI, the varying perspectives on PPI and the motivations of the patients and public involved . A large body of research focuses on PPI in health research, particularly in more recent years. However, the specific role of patient and public involvement facilitators (PPIFs) remains under‐researched.…”
Section: Introductionmentioning
confidence: 99%
“…highlight the benefits and challenges of lay involvement in a research team focusing on qualitative data analysis. Jinks et al . stress that the research team's institution must support a sustainable environment which allows the patient voice to be heard in all aspects of research.…”
mentioning
confidence: 99%